HLA-B27-ASSOCIATED UVEITIS: EPIDEMIOLOGY, CLINICAL PICTURE, AND COMPLICATIONS - T. V. Dubinina; A. B. Demina; Sh. F. Erdes (Научно-практическая ревматология)
Anterior uveitis is the most common form of intraocular inflammation. Among them, HLA-B27-associated uveitis occupies one of the leading places, which may be an independent disease or one of the manifestations of spondy- loarthritis (SA). The paper considers the general issues of the nomenclature and classification of uveitis, by using the classification criteria of the International Uveitis Study Group and the Standardization of Uveitis Nomenclature Workshop. The epidemiological aspects of uveitis are described. Emphasis is laid on a difference in the detection rate of uveitis in different countries, in men and women, as well as in different forms of SA. The clinical features of SA- associated uveitis and its complications are discussed.